Optimization of Promotional Media through Instagram Feeds Design using Figma at Nawak Gym Singosari - Ariansyah, Azriel; Tri Istining Wardani; Heru Utomo (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This research aims to design Instagram feed designs as a digital promotional medium to increase brand awareness at Nawak Gym Singosari. Based on observations, conventional promotional methods were considered less effective, while the utilization of Instagram as a promotional platform had not been optimally developed. This study employs an action research method using the spiral model consisting of two cycles, each including the stages of planning, action, observation, and reflection. Data were collected through interviews, observations, documentation, and questionnaires involving 30 respondents, including gym owners, staff, design experts, marketing experts, and potential members. The effectiveness of the Instagram feed designs was measured using a rating scale technique across two research cycles. The results show that the effectiveness score increased from 2.7 in the first cycle to 4.4 in the second cycle, indicating a significant improvement. The developed Instagram feed designs proved to be highly effective as a promotional medium, enhancing audience attention, interest, and brand identity. Therefore, the @nawakgym Instagram feed design is recommended for implementation as an effective and sustainable digital promotional strategy.